Development of Cognitive Learning Scale to Test the Knowledge of Poultry Farmers - Goswami, A.; Ghosh, R. K.; Biswas, S. (International Journal of Bio-resource and Stress Management, 2023)
Three hundred and thirty six items were initially constructed on the basis of promoting thinking rather than rote memorization and differentiated the well informed poultry farmers from the poorly informed ones. The scores from sample respondents were subjected to item analysis, comprising of item difficulty index and item discrimination index. In the final selection, the scale consisted of 39 items with difficulty index ranging from 30 to 80 and discrimination index ranging from 0.30 to 0.55. The reliability of the knowledge test developed was tested by split-half and test-retest method. The co-efficient of correlation values in split-half and test-retest method were 0.88 and 0.85, respectively which were found to be significant at 1% level of significance. It was found that knowledge test constructed was highly stable and dependable for measurement.